Effect of Cryotherapy Combined with William Flexion Exercise in Reducing Myogenic Low Back Pain - Yoga Handita Windiastoni; Nur Basuki; Nurul Fithriati Haritsah (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Health problems related to daily activities can be experienced by individuals or groups. The most common complaint in the musculoskeletal system is low back pain. Low Back Pain according to the Ministry of Health of the Republic of Indonesia in 2018 means pain that is felt in the lower back area, between the lowest costal angle to the sacrum. The purpose of this study was to determine the effect of adding cold pack therapy to the William flexion exercise on reducing pain in myogenic LBP patients. Subjects and Method: This was an experiment study conducted at Dr. Moewardi Hospital, Surakarta, Central Java, in September 2022. A sample of 22 patients with myogenic low back pain was allocated into two groups. The dependent variable was pain. The independent variable was cryotherapy combined with William flexion exercise. Pain was measured using quadripel visual analogue scale. Mean between groups after intervention was analyzed using independent t test. Results: Mean of pain in the intervention group (Mean= 6.27; SD= 1.00) was lower than control group (Mean= 7.09; SD= 0.94), and it was statistically significant (p<0.001). Conclusion: Cryotherapy combined with William flexion exercise is better to reduce pain in patients with myogenic low back pain. Keywords: low back pain myogenic, cryotherapy, William flexion exercise. Correspondence: Yoga Handita Windiastoni. Study Program of Physiotherapy, Health Polytechnic, Ministry of Health Surakarta, Karanganyar, Central Java. Email: handitayoga@gmail.com. Mobile: 081329036114.